2020
DOI: 10.1158/0008-5472.can-19-2733
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Regulation of ΔNp63 by TGFβ-Regulated miRNAs Is Essential for Cancer Metastasis

Abstract: ∆Np63 is a transcription factor of the p53 family and has crucial functions in normal development and disease. The expression pattern of ∆Np63 in human cancer suggests dynamic regulation of this isoform during cancer progression and metastasis. Many primary and metastatic tumors express high levels of ∆Np63, while ∆Np63 loss is crucial for tumor dissemination, indicating an oscillatory expression of ∆Np63 during cancer progression. Here we use genetically engineered orthotopic mouse models of breast cancer to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 63 publications
2
19
1
Order By: Relevance
“…Those data are opposite to previous findings where mutant p53 inhibited p63 only in the presence of TGFβ, through the formation of a mutant p53/Smad/p63 complex [163]. Alternatively, TGFβ may inhibit ΔNp63 through Smad3, which induces ΔNp63‐targeting miRNAs [164]. There is also evidence for a stimulatory role of BMP4/SMAD signalling on ΔNp63 in normal epithelium [165,166].…”
Section: Signalling Pathways That Regulate P63 Levels or Activitycontrasting
confidence: 70%
“…Those data are opposite to previous findings where mutant p53 inhibited p63 only in the presence of TGFβ, through the formation of a mutant p53/Smad/p63 complex [163]. Alternatively, TGFβ may inhibit ΔNp63 through Smad3, which induces ΔNp63‐targeting miRNAs [164]. There is also evidence for a stimulatory role of BMP4/SMAD signalling on ΔNp63 in normal epithelium [165,166].…”
Section: Signalling Pathways That Regulate P63 Levels or Activitycontrasting
confidence: 70%
“…Importantly, restoration of ΔNp63α expression effectively rescues TGF-β-induced EMT, cell migration, and tumor metastasis. Notably, it is also reported that activation of TGF-β can inhibit ΔNp63α expression through the Smad-mediated up-regulation of several miRNAs [ 48 ]. Therefore, it appears that TGF-β can regulate ΔNp63α expression at multiple levels, including antagonized p63 transactivation function by mutant p53-Smads interplay, transcriptional suppression of p63, posttranscriptional regulation via miRNAs, or reduced protein stability as shown in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in basal-like breast cancer, leader cells showed high motility, co-expressed epithelial (miR-205) and mesenchymal (ZEB2) expression, and retained cell-cell adhesion. This ‘partial EMT’ program was driven by ΔNP63α [ 143 ], which was found to be a “phenotypic stability factor” for hybrid E/M phenotype [ 83 ] and a downstream target of TGF-β signaling [ 144 ]. In luminal breast cancer, the leader cells exhibited molecular signatures of partial EMT and collective invasion, and were able to switch back and forth to a follower cell phenotype during collective migration.…”
Section: Role Of Partial Emt In Collective Migrationmentioning
confidence: 99%